The intellectual trajectory of Manuel Zapata Olivella in Afro-Colombian organizational processes - Valderrama Rentería, Carlos Alberto (Meridional. Revista Chilena de Estudios Latinoamericanos, 2021)
In this article, I examine the intellectual trajectory of Manuel Zapata Olivella in the Afro-Colombian organizational process. I suggest that he was a committed intellectual. I will focus on two aspects of his trajectory. First, I study the way in which Manuel Zapata Olivella connected to Afro-Colombian organizations, groups, and intellectuals to discuss issues related to black identity and racism in Colombia. I believe that Manuel Zapata Olivella was a key factor in during the emergence of the Afro-Colombian public spheres. Second, I study the conflicts and contradictions that emerged from these discussions. I suggest that these Afro-Colombian public spheres were a terrain ideologically disputed and contested.